An Anthropological Approach to Didactics in Fluid Mechanics Education to Bridge Cultural Contexts and Engineering Principles - Díaz, José Luis; González, Julián Roa (Gemilang Maju Publikasi Ilmiah (GMPI), 2024)
The Anthropological Theory of Didactics (ATD) provides a lens through which knowledge is viewed in its sociocultural context. Originally rooted in mathematics education, its application has expanded to diverse disciplines, including engineering. This article delves into the intersection of fluid mechanics, a crucial branch of engineering, with ATD. Core tenets of ATD, such as the cultural context of knowledge, praxeologies, and didactic transposition, are explored in relation to engineering principles. The emphasis is on contextual understanding, problem-solving, collaboration, tool usage, and continuous improvement. Fluid mechanics, vital in areas like aerospace and civil engineering, is intertwined with ATD to address student misconceptions. The article proposes five activities to effectively integrate ATD in fluid mechanics education, drawing from daily life, historical contexts, and traditional tools. These activities aim to bridge theoretical concepts with tangible experiences, fostering a comprehensive understanding of fluid mechanics within cultural contexts.